Cultural Design - Gumelar, Michael Sega (an1mage, 2017)
Cultural is a construction runs on an ongoing basis from a bad to a better direction from and for humans in an environment to achieve prosperity, happiness and peace of all people in an area. Clash of cultural is a necessity that is inevitable in the era of information and globalization. There is a strong cultural dominance in globalization to imply a false consciousness to the younger generation and its hegemonic. Even some people being hegemony information slaves (hegeformaslaves) by cultural and sadly they do not even realised it. There is a cultural resistance, adaptation, and acculturation occur. When thinking about the need for a strong cultural identity, the need for redigging, reshaping, and finding again the ancestral identity to be used as construction of new cultural identities as a unifying with the goal of unity, prosperity, happiness and peace in a community.   This globalization era required a local merger with global thought that does not cancel each other out, but belong together and complete it. Thinking